Tristana Reluz and María Eugenia Alonso, Pianists: Notes on The Role of Music in Tristana by Benito Pérez Galdós and Ifigenia by Teresa De La Parra - Forcadell, Joan Antoni (2021)
This article analyzes how two novels published in different contexts, Tristana (1892), by Benito Pérez Galdós, and Ifigenia (1924), by Teresa de la Parra, use music to address the women’s issue in the respective societies in which its protagonists are inserted. Through a contrastive analysis, constructive parallels are pointed out that are fundamental to unravel the meaning of their disputed ends and that, ultimately, allow us to see in music a first-order thematic component in the articulation of their respective narrative structures. Both Tristana Reluz and María Eugenia Alonso see in the development of their piano skills a means of professionalization and emancipation that is frustrated by instances and circumstances beyond their control. We conclude by pointing out specular trajectories in the face of similar crossroads, in both cases paradoxical: while the attempts of rebellion in María Eugenia, channeled through art, end up being innocuous, and her integration into social institutions is complete, Tristana ends up developing an overwhelming artistic personality in a mutilated body that has suffered all possible social transgressions, but her reintegration is impossible.